Keabsahan Tindakan Pemerintah Dalam Pemberhentian Dan Pengangkatan Pengganti Anatarawaktu Anggota Saniri Negeri - Galeb, Yunasril La; Nendissa, Renny Heronia; Saija, Vica Jillyan Edsti (PATTIMURA Law Study Review, 2024)
ABSTRACT: In carrying out or issuing decisions or actions, the government must determine based on authority, in Article 8 paragraph (2) of Law Number 30 of 2014 concerning Government Administration states that: "Government bodies and/or officials in using authority must be based on: a. Legislation. b. General principles of good government.” The dismissal and appointment of interim replacements for State Saniri members is regulated in Ambon City Regional Regulation Number 8 of 2017 concerning the State, in this case in Article 67, namely: "The interim membership of State Saniri is determined by the Mayor's Decree on the recommendation of the State Saniri Leadership through the Head of State Government" and Article 68 paragraph (1): "Members of Saniri Negeri resign because: a. Died. b. Own request; and c. dismissed." As well as paragraph (3) which states that: "Replacement of members of the Saniri Negeri who quit as referred to in paragraph (1) is proposed by the chairman of the Saniri Negeri to the Soa concerned no later than 14 (fourteen) days." However, in fact, the Mayor of Ambon issued Ambon Mayor Decree Number 447 of 2022 which in the Consideration considering letters a and b of the object of the decision is a letter from the Acting Head of the Batu Merah State Government regarding the follow-up to the interim replacement proposal. Meanwhile, the leadership of Saniri Negeri Batu Merah never made a proposal to the Acting Batu Merah, Head of Sirimau District, and Mayor of Ambon to dismiss and/or replace members of Saniri Negeri Batu Merah. The type of research carried out is a normative juridical research type carried out through literature review or secondary materials.